Aspiculuris mexicana n. sp. (Nematoda: Heteroxynematidae) parasite of Cricetidae rodents from Mexico, with a taxonomic key for the species of the genus - Christina Lynggaard; Luis García-Prieto; Carmen Guzmán-Cornejo; David Osorio-Sarabia (Revista Mexicana de Biodiversidad)
During November 2010, a tarabundí vole, Microtus oaxacensis Goodwin, 1966 and 2 Mexican harvest mice, Reithrodontomys mexicanus Sassure, 1860 collected in Oaxaca, Mexico, were examined for helminths. The nematode Aspiculuris mexicana n. sp., was found in the colon of both species. This parasite is characterized by 2 clear synapomorphies: 1) cervical alae ending abruptly at the middle-length of esophageal bulb, and 2) the presence of 16 caudal papillae with unique arrangement: 3 preanal pairs; 1 pair adanal; a single papilla immediately postanal; 2 postanal pairs; 1 single ventral papilla, and 1 ventral pair far away from the anus. In addition, this work presents an updated taxonomic key for 17 of the 20 valid species included in the genus.